152 Stem Cell Coated Metallic Coronary Stents Show Accelerated Strut Coverage without Excessive Neointimal Proliferation in a Porcine Model. (31st May 2014) - Raina, Tushar; Arnold, Nadine; Moore, Harry; Aflatoonian, Behrouz; Walsh, Jim; Whitehouse, Sam; Al-Lamee, Kadem; Francis, Sheila; Gunn, Julian; Iqbal, Javaid
Abstract : Introduction: The success of percutaneous coronary intervention (PCI) has been limited by restenosis and stent thrombosis. Delayed or incomplete endothelial regeneration is believed to be a key factor responsible for these events. Developing a stent with an accelerated healing profile may be of benefit. We aimed to evaluate the feasibility and safety of seeding a bare metal stent (BMS) with human trophoblastic endovascular progenitor cells (hTEC) derived from human embryonic stem cells. Methods: hTEC were derived by the terminal differentiation of trophoblast stem cells while the latter were derived as distinct trophoblast cell lines from human embryonic stem cells. BMS were seeded with hTEC by co-culturing for 3 days. The biodistribution and fate of hTEC were studied using radiolabeled 111 Indium oxine and fluorescent in-situ hybridisation. A porcine coronary artery model was used to compare the rate and extent of endothelial regeneration and the degree of neointimal proliferation. Results: Characterisation of hTEC confirmed a mixed progenitor and endothelial cell phenotype. For the stents seeded with 111 Indium-labelled hTEC, the radioactivity measured over the explanted stented LAD was 77, 642 cpm at 1 h, 20, 048 cpm at 1 day and 2, 323 cpm at 7 days, with no significant radioactivity detected at any of the distal sites including blood vessels, heart, lung, spleen, liver and kidneys. Scanning electron microscopy showed earlier endothelial coverage in hTEC-seeded stents as compared to similar BMS (Figure 1 ). hTEC-seeded BMS achieved complete stent coverage in 3 days (Figure 2 ). Quantitative coronary angiography, intravascular ultrasound assessment and histomorphometry showed no difference in neointimal hyperplasia between hTEC-seeded and control BMS (Figure 2 ). Conclusion: hTEC seeding of coronary stents is a novel and safe approach to accelerate endothelial regeneration without increasing neointimal proliferation.